Pengaruh Green Intellectual Capital terhadap Kinerja Keuangan dengan Family Ownership sebagai Variabel Moderasi - Br Sagala, Efi Noviarta; Setiawati, Rike; Solikhin, Agus (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the effect of green intellectual capital (GIC) which consists of green human capital, green structural capital, and green relational capital on financial performance (measured by Return on Assets/ROA) with family ownership as a moderating variable. The population in this study is family firms listed on the Indonesia Stock Exchange (IDX) for the 2019- 2022 period. This research uses a quantitative approach with the sampling method used is purposive sampling with a sample of 36 companies for a period of 4 consecutive years so that the total sample is 144. Data analysis uses multiple linear regression analysis and Moderrated Regression Analysis (MRA) using the SPSS version 26 application. The results of this study show that green intellectual capital has a negative and significant effect on financial performance. Meanwhile, family ownership is unable to moderate the effect of green intellectual capital on financial performance.